Dedicated isotropic 3-D T1 SPACE sequence imaging for radiosurgery planning improves brain metastases detection and reduces the risk of intracranial relapse. (August 2022) - Kutuk, Tugce; Abrams, Kevin J.; Tom, Martin C.; Rubens, Muni; Appel, Haley; Sidani, Charif; Hall, Matthew D.; Tolakanahalli, Ranjini; Wieczorek, D. Jay J.; Gutierrez, Alonso N.; McDermott, Michael W.; Ahluwalia, Manmeet S.; et al.
Highlights: Dedicated SRS imaging with MPRAGE and SPACE improved detection of brain metastases. This approach was associated with a significant decrease in the incidence of DIF. The benefit of MPRAGE with SPACE was more pronounced for patients undergoing their first SRS course. This represents a practical solution to a commonly encountered problem in clinical practice. Abstract: Background: Stereotactic radiosurgery (SRS) is increasingly used for brain metastases (BM) patients, but distant intracranial failure (DIF) remains the principal disadvantage of this focal therapeutic approach. The objective of this study was to determine if dedicated SRS imaging would improve lesion detection and reduce DIF. Methods: Between 02/2020 and 01/2021, SRS patients at a tertiary care institution underwent dedicated treatment planning MRIs of the brain including MPRAGE and SPACE post-contrast sequences. DIF was calculated using the Kaplan–Meier method; comparisons were made to a historical consecutive cohort treated using MPRAGE alone (02/2019–01/2020). Results: 134 patients underwent 171 SRS courses for 821 BM imaged with both MPRAGE and SPACE (primary cohort). MPRAGE sequence evaluation alone detected 679 lesions. With neuroradiologists evaluating SPACE and MPRAGE, an additional 108 lesions were identified ( p  < 0.001). Upon multidisciplinary review, 34 additional lesions were identified. Compared to the historical cohort (103 patients, 135 SRS courses, 479 BM), the primary cohort had improved median time to DIF (13.5 vs. 5.1 months, p  = 0.004). The benefit was even more pronounced for patients treated for their first SRS course (18.4 vs. 6.3 months, p  = 0.001). SRS using MPRAGE and SPACE was associated with a 60% reduction in risk of DIF compared to the historical cohort (HR: 0.40; 95% CI: 0.28–0.57, p  < 0.001). Conclusions: Among BM patients treated with SRS, a treatment planning SPACE sequence in addition to MPRAGE substantially improved lesion detection and was associated with a statistically significant and clinically meaningful prolongation in time to DIF, especially for patients undergoing their first SRS course.